1H NMR Study of Chiral Monoaza-15-crown-5 Ether Derivative by Relaxation Time T1 - ASKIN, MUZAFFER; ZAFER KOYLU, M.; TUTSI, MIZGIN (Asian Journal of Chemistry, 2010)
Measurement of spin-lattice relaxation time T1 has been performed for the chiral monoaza-15-crown-5 ether derivative as a function of temperature. Activation energies Ea and correlation times ( τc) were obtained. The data suggest that the underlying mechanism of relaxation is due to magnetic dipole-dipole interaction.